Criticality of Benzoyl Peroxide and Antibiotic Fixed Combinations in Combating Rising Resistance in Cutibacterium acnes - Ghannoum M; Gamal A; Kadry A; Del Rosso JQ; Stein Gold L; Kircik LH; Harper JC (Clinical, Cosmetic and Investigational Dermatology)
Mahmoud Ghannoum,1,2 Ahmed Gamal,1 Ahmed Kadry,1 James Q Del Rosso,3– 5 Linda Stein Gold,6 Leon H Kircik,7– 9 Julie C Harper10 1Department of Dermatology, Case Western Reserve University, Cleveland, OH, USA; 2University Hospitals Cleveland Medical Center, Cleveland, OH, USA; 3JDR Dermatology Research/Thomas Dermatology, Las Vegas, NV, USA; 4Advanced Dermatology and Cosmetic Surgery, Maitland, FL, USA; 5Touro University Nevada, Henderson, NV, USA; 6Department of Dermatology, Henry Ford Hospital, Detroit, MI, USA; 7Department of Dermatology, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 8Department of Dermatology, Indiana University School of Medicine, Indianapolis, IN, USA; 9Physicians Skin Care, PLLC, DermResearch, PLLC, and Skin Sciences, PLLC, Louisville, KY, USA; 10Dermatology & Skin Care Center of Birmingham, Birmingham, AL, USACorrespondence: Mahmoud Ghannoum, University Hospitals Cleveland Medical Center, 11100 Euclid Avenue, Wearn 311, Cleveland, OH, 44106-5028, USA, Tel +1 216-844-8580, Fax +1 216-844-1076, Email mag3@case.eduBackground: Antibiotic resistance is growing globally, with multiple countries reporting resistance in > 50% of Cutibacterium acnes (C. acnes) strains. Combination formulations of an antibiotic and the antimicrobial benzoyl peroxide (BPO) may reduce this resistance risk, especially with prolonged use. This 4-part study tested susceptibility of 31 C. acnes clinical strains and development of resistance to antibiotics alone or combined with BPO.Methods: C. acnes susceptibility to single-drug antibiotics was assessed via minimum inhibitory concentration (MIC) values obtained from epsilometer tests, with lower MIC indicating higher susceptibility. Susceptibility to fixed-dose antibiotic/BPO combination products was determined by measuring the zone of inhibition using the agar diffusion method, with larger diameter indicating increased bacterial inhibition. The effect (synergistic, additive, antagonistic, or indifferent [no interaction]) of combining clindamycin with BPO on C. acnes inhibition was evaluated using a checkerboard assay, wherein 2 test compounds are combined in varying concentrations. Resistance development was assessed using serial passage of bacterial cultures in increasing concentrations of clindamycin alone or in combination with BPO.Results: All tested antibiotics (clindamycin, doxycycline, erythromycin, and minocycline) exhibited similar activity. C. acnes susceptibility was variable, with some strains having elevated MIC values—an indication of resistance—against different antibiotics. For 6 strains resistant to clindamycin alone (inhibitory zone=0 cm), formulations with BPO enhanced activity against the same isolates (range: 0.8– 2.2 cm). Of 7 acne-associated strains, combining clindamycin and BPO had an additive effect against 4, and no interaction against 3. Bacterial cultures repeatedly exposed to the combination of clindamycin and BPO did not develop antibiotic resistance, which occurred with exposure to clindamycin alone.Conclusion: Overall, antibiotic susceptibility was highly dependent on the C. acnes strain, and antibiotic formulations with BPO exhibited enhanced activity against less susceptible strains. Fixed combinations of BPO with an antibiotic may improve antimicrobial activity and protect against resistance development.Keywords: acne, antibiotics, benzoyl peroxide, clindamycin, combination treatment, C. acnes, resistance, susceptibility